Agricultural zoning as tool for expansion of cassava in climate change scenarios - Oliveira Aparecido, Lucas Eduardo de; Silva Cabral de Moraes, Jose Reinaldo da; Meneses, Kamila Cunha de [UNESP]; Lorencone, Pedro Antonio; Lorencone, Joao Antonio; Olanda Souza, Gabriel Henrique de; Torsoni, Guilherme Botega (Springer, 2020)
Improvement of planting season and crop growth time, considering climatic and soil needs of plants, is important to increase cassava (Manihot esculenta) production in Midwestern Brazil. Thus, we sought to develop an agricultural zoning for cassava cultivation in the Midwest of Brazil in different climate change scenarios. Mean air temperature and precipitation data from localities of the Midwest of Brazil were obtained from the Brazilian National Institute of Meteorology (INMET). Clay (%) data from localities of the Midwest of Brazil were obtained from SoilGrids. Regions where the air temperature was within the range from 20 to 27 degrees C were considered climatically favorable for commercial exploitation of cassava, in addition to precipitation between 1000 and 1500 mm year(-1), and clay content was less than <= 35%. Moreover, regions with air temperature below 16 degrees C and above 38 degrees C, precipitation below 1000 mm and above 1500 mm year(-1), and clay content > 35% were considered unsuitable for cassava cultivation. Raster or matrix images, corresponding to mean annual air temperature, annual precipitation, and clay (soil), were superimposed to create cassava suitability classes, according to crop requirements. The climate change scenarios were established by changing the air temperature (degrees C) and rainfall (mm). The air temperature was increased by 1.5, 3.0, 4.5, and 6.0 degrees C as adopted by Pirttioja et al. (Clim Res 65:87-105, 2015). We changed in precipitation - 30, - 15, + 15, and 30% according to the future projections simulated by the IPCC (2014). Maps were made using geographic information systems. In the states of Mato Grosso do Sul, Mato Grosso, and Goias, mean precipitation was around 1200 to 4000 mm year(-1). Northern Mato Grosso showed the highest annual precipitation, with values above 3500 mm. A large extension of the Midwest region of Brazil is climatically and soil favorable for cassava. The Midwest is a region with high rainfall, so we recommend planting in well-drained soils to avoid phytosanitary problems. Producers taking this care can plant cassava in 86.6% of the territory. The climate change scenarios demonstrated different Agriculture zonings for cassava in the Midwest of Brazil. With the increase in air temperature, greater marginal classes occurred, but cassava is resistant to this condition. But, this increase in temperature can reduce the cycle and consequently reduce production.